SEKSUALITAS PEREMPUAN DALAM BUDAYA PATRIARKHI - Danik Fujiati (Muwazah, 2016)
This paper examines the culture of patriarchy, which dominate and discriminate against women. Control of patriarchy on female sexuality, making them no longer have authority over his own body. Culture that built into the foundations of a patriarchal society with control over female sexuality, be threatening the existence of women was regarded as liyan, so that it becomes the root of the problem of gender inequality. Contributions patriarchy over the control of women's sexuality, make women experiencing the condition in which, when there are any problem affecting the female body (biological), then it happens because women's own fault. Ironically, in a society characterized by patriarkhisme, then the control, domination and discrimination both in the public and domestic over women's bodies become considered reasonable by the community, even countries.Paper ini mengkaji tentang budaya patriarkhi yang mendominasi dan mendiskriminasi kaum perempuan. Kontrol patriarkhi terhadap seksualitas perempuan, menjadikan mereka tidak lagi memiliki otoritas atas tubunya sendiri. Kultur yang dibangun dalam pondasi masyarakat patriarkhi dengan kontrol atas seksualitas perempuan mengancam eksistensi perempuan yang dianggap sebagai liyan, sehingga menjadi akar masalah ketidakadilan gender. Kontribusi patriarki atas kontrol terhadap seksualitas perempuan menjadikan kaum perempuan mengalami kondisi dimana, ketika ada masalah apapun yang menimpa tubuh perempuan (biologis), maka hal tersebut terjadi karena kesalahan perempuan sendiri. Ironis lagi, dalam masyarakat yang diwarnai oleh patriarkhisme, maka penguasaan, dominasi dan diskriminasi baik di ranah publik maupun domestik atas tubuh perempuan menjadi hal yang dianggap wajar oleh masyarakat, bahkan negara.